Synthetic approaches to marine labdane diterpenes - Wisch, Gregory Albert (Rhodes University, Faculty of Science, Department of Chemistry, 2002)
The work presented in this thesis describes the synthesis of labd-13-en-8ÃŸ, 15-diol (46) a stable reduced derivative of an unstable marine natural product aldehyde [8ÃŸ-hydroxylabd-13E-en-15-al (6)] isolated by Cimino, et al. from the skin of a Notaspidean mollusc Pleurobranchaea meckelii. The rationale for the synthesis was to provide sufficient 46 for eventual mild oxidation to 6 and investigation of the biological activity of this latter compound. (-)-Sclareol (32), a common diterpene synthetic precursor, was the starting point for the ten step synthesis of 46 described in this thesis. A search of the literature revealed that only one non stereospecific synthesis of 46 had been previously reported. To provide the necessary background to the synthetic component of this thesis, both the occurrence of labdane and ent-labdane in the marine environment and the use of sclareol in the synthesis of marine natural products, was reviewed. The initial step in the synthesis of 46 was the potassium permanganate oxidation of sclareol to give a bisnorlabdane ketone. Reduction of this ketone with lithium aluminium hydride produced a mixture of diols which, through t-butyldimethysilyl triflate protection, afforded a quantitative route to protecting the C-13 ketone in an effort to prevent unwanted intramolecular cyclization reactions. Dehydration of the tertiary alcohol moiety at C-8 with phosphorous oxychloride yielded the Î”â ¸Â·Â¹â µ exocyclic alkene required for the next oxidation step. Ozonolysis succeeded in producing the desired C-8 ketone after much deliberation and research into alternative oxidation strategies. Methyl lithium methylation quantitatively afforded the desired a-methyl substitution at C-8, identified at the onset as the key step in the synthesis. Tetra-butylarnmonium fluoride deprotection yielded the 8ÃŸ,13-dihydoxylated product, which was in turn subjected to a Swern oxidition to give the desired 8ÃŸ-hydroxy-bisnorlabda-13-one. A modified Horner-Wadsworth-Emmons reaction allowed for elaboration at C-13 to yield a to Î”Â¹Â³ olefin with a terminal C-15 ethyl ester. Diisobutylaluminium hydride reduction of the ester produced the desired labd-13-en-8ÃŸ, 15-diol (46) in a low overall yield of 3.4%. Although opportunities for optimization of at least three steps in the synthesis exist, time constraints prevented both optimization of these steps and an investigation of the oxidation of 46 to 6.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Diterpenes